Frugality : Are We Fretting Too Much? Household Saving and Assets in the United States - Tanner, Evan (IMF Working Papers; Working Paper ;, 2009)
Household savings rates in the United States have recently crept up from all-time lows. Some have suggested that a shift toward frugality will hamper GDP growth-the Keynesian "paradox of thrift." We estimate that households compensate for a fall in their asset income by saving more out of their labor income, dollar-for-dollar. In the wake of the crisis, our model predicts that such primary savings will increase, but only temporarily and modestly, as household assets stabilize. As savings flows gradually accumulate, they help rebuild corporate net worth and hence firms' capacity to make capital investments. A timely return to pre-crisis levels of capital investment would require that U.S. households save substantially more than the model predicts, starting now. Hence, we should fret that our savings rates may be too low.